Predictors of Corporal Punishment during the COVID-19 Pandemic - Robert D. Sege; Eliza Loren Purdue; Dina Burstein; Phyllis Holditch Niolon; Lori Lyn Price; Ye Chen; Elizabeth A. Swedo; Tammy Piazza Hurley; Kavita Prasad; Bart Klika (MDPI AG, 2024)
Although current policies discourage the use of corporal punishment (CP), its use is still widespread in the US. The objective of this study was to assess the proportion of parents who used CP during the pandemic and identify related risk and protective factors. We analyzed results of a nationwide cross-sectional internet panel survey of 9000 US caregivers who responded in three waves from November 2020 to July 2021. One in six respondents reported having spanked their child in the past week. Spanking was associated with intimate partner violence and the use of multiple discipline strategies and not significantly associated with region or racial self-identification. Parents who spanked sought out more kinds of support, suggesting an opportunity to reduce spanking through more effective parenting resources. Additionally, these results suggest that parents who report using CP may be at risk for concurrent domestic violence.